1982
DOI: 10.1136/ard.41.6.579
|View full text |Cite
|
Sign up to set email alerts
|

Histopathology of the synovial membrane of peripheral joints in ankylosing spondylitis.

Abstract: SUMMARY The histological features of the synovial membrane of peripheral joints in ankylosing spondylitis are similar to those seen in rheumatoid arthritis. There is intimal cell hyperplasia, a diffuse lymphocyte and plasma cell infiltrate, and formation of lymphoid follicles. Peroxidaseantiperoxidase staining shows the presence of IgG-, IgA-, and IgM-containing plasma cells in ankylosing spondylitis. The percentage of IgM-containing cells is significantly lower in ankylosing spondylitis than in rheumatoid art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
20
0
3

Year Published

1988
1988
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(28 citation statements)
references
References 14 publications
5
20
0
3
Order By: Relevance
“…Unlike new bone formation in the axial spine, synovial inflammation within the hip joint induces bone erosion and subsequent joint destruction 4,5 in AS. Additionally, the histological appearance of the synovial membrane of the hip joint in patients with AS is similar to that observed in RA 6 . These results suggest that both osteoproliferative and osteodestructive changes may occur in parallel at different sites in AS.…”
Section: To the Editorsupporting
confidence: 49%
“…Unlike new bone formation in the axial spine, synovial inflammation within the hip joint induces bone erosion and subsequent joint destruction 4,5 in AS. Additionally, the histological appearance of the synovial membrane of the hip joint in patients with AS is similar to that observed in RA 6 . These results suggest that both osteoproliferative and osteodestructive changes may occur in parallel at different sites in AS.…”
Section: To the Editorsupporting
confidence: 49%
“…The SM in a variety of spondylarthropathies may be variable. Some reports of the SM in ankylosing spondylitis suggest similarities to RA (16), while we and other investigators have reported prominent vascular changes, including differential adhesion molecule expression, in PsA SM (2,3). In addition, specific ultrastructural abnormalities have previously been described in electron microscopy studies of PsA SM (4).…”
mentioning
confidence: 88%
“…Существенных гистологических особенностей синовита при СПА по сравнению с синовитом при РА, как правило, не отмечается. Наблюдаются гиперплазия поверх-ностного слоя синовиальной оболочки, диффузная лимфо-цитарная и плазматическая инфильтрация и образование лимфоидных фолликулов, повышенная васкуляризация [3]. Однако результаты отдельных исследований отличаются.…”
unclassified
“…Главным достоинством эторикоксиба является высокий уровень безопасности в отношении желудочно-кишечного тракта (ЖКТ), что доказано в большом числе РКИ, часть из которых плацебоконтролируемые, и соответствующем ме-таанализе, а также двух масштабных «эндоскопических» ис-следованиях [3,4]. Поскольку эторикоксиб относится к вы-сокоселективным НПВП (коксибам), огромное внимание исследователей было приковано к проблеме осложнений со стороны сердечно-сосудистой системы.…”
unclassified